AUGMENTED REALITY CHILDREN STORYBOOK TIMUN MAS MEMBENTUK PERSEPSI VISUAL ANAK USIA DINI - Erste Panggayuh Putri, Kinanti (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
Technology-based visual literacy reading activities are an implementation of the smart education concept that is starting to be popularly introduced to the digital native generation. The strategy to combine the power of visual-based learning media and virtual reality technology is a new innovation that seeks to present a more interesting and enjoyable reading experience for early childhood. The research aims to examine how the Augmented Reality Children Storybook (ARCS) Timun Mas media can shape early childhood cognitive-visual responses. The research was conducted using a qualitative case study method on children aged 4-6 years at Darrunajwa Kindergarten, Jombang District, East Java. The data collection techniques chosen to obtain in-depth information were observation, interviews, literature study, and documentation. The results showed that the Augmented Reality-based Timun Mas storybook media can form five indicators of children's visual-cognitive abilities including visual sensory, visual attantion, visual memory, visual spatial relation, and visual sequention memory. The visual response will then form a better visual perception of children towards the forms of visual elements, storylines to moral messages contained in the ARCS Timun Mas.